Pemahaman dan Realitas Implementasi Workplace Spirituality dalam Perencanaan dan Pelaksanaan Anggaran - iismiati, iismiati; Dwirandra, A.A.N.B (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.03.TAHUN 2018, 2018)
This research is motivated by a whole human concept that has not been fully implemented in the workplace, as most people consider the workplace is a place to seek something worldly by forgetting the inner life and ignoring religious values. The purpose of this research is to understand the reality of workplace spirituality in planning and implementation of budget. Research data obtained through in-depth interviews and participatory observation then it is analyzed by Interpretative Phenomenological Analysis . The results of the study interpret the understanding of  informant's about workplace spirituality understanding into 3 (three) perspectives namely  intrinsic views, religious views, and existentialist views. The reality of workplace spirituality in planning and implementation of budget has not been fully compatible with its understanding because of deviations and  the behavior of the apparatus still ignores the spiritual  values. The dissonance between reality of workplace spirituality in planning and implementation of budget with understanding  of workplace spirituality is required the controlling factors such as leadership superstructure, work environment, and personal value.